A novel IgG-based FLT3xCD3 bispecific antibody for the treatment of AML and B-ALL - Melanie Märklin; Gundram Jung; Jonas S Heitmann; Joseph Kauer; Helmut R Salih; Stefanie Mueller; Bochong Li; Latifa Zekri; Naveen K Mehta; Martin Pfluegler; Kristan Meetze; Isabelle Sindel; et al. (Journal for ImmunoTherapy of Cancer)
Background In lymphoid malignancies, the introduction of chimeric antigen receptor T (CAR-T) cells and bispecific antibodies (bsAbs) has achieved remarkable clinical success. However, such immunotherapeutic strategies are not yet established for acute myeloid leukemia (AML), the most common form of acute leukemia in adults. Common targets in AML such as CD33, CD123, and CLEC12A are highly expressed on both AML blasts and on normal myeloid cells and hematopoietic stem cells (HSCs), thereby raising toxicity concerns. In B-cell acute lymphoblastic leukemia (B-ALL), bsAbs and CAR-T therapy targeting CD19 and CD22 have demonstrated clinical success, but resistance via antigen loss is common, motivating the development of agents focused on alternative targets. An attractive emerging target is FLT3, a proto-oncogene expressed in both AML and B-ALL, with low and limited expression on myeloid dendritic cells and HSCs.Methods We developed and characterized CLN-049, a T cell-activating bsAb targeting CD3 and FLT3, constructed as an IgG heavy chain/scFv fusion. CLN-049 binds the membrane proximal extracellular domain of the FLT3 protein tyrosine kinase, which facilitates the targeting of leukemic blasts regardless of FLT3 mutational status. CLN-049 was evaluated for preclinical safety and efficacy in vitro and in vivo.Results CLN-049 induced target-restricted activation of CD4+ and CD8+ T cells. AML cell lines expressing a broad range of surface levels of FLT3 were efficiently lysed on treatment with subnanomolar concentrations of CLN-049, whereas FLT3-expressing hematopoietic progenitor cells and dendritic cells were not sensitive to CLN-049 killing. Treatment with CLN-049 also induced lysis of AML and B-ALL patient blasts by autologous T cells at the low effector-to-target ratios typically observed in patients with overt disease. Lysis of leukemic cells was not affected by supraphysiological levels of soluble FLT3 or FLT3 ligand. In mouse xenograft models, CLN-049 was highly active against human leukemic cell lines and patient-derived AML and B-ALL blasts.Conclusions CLN-049 has a favorable efficacy and safety profile in preclinical models, warranting evaluation of its antileukemic activity in the clinic.